Supramolecular Self-Assemblies Incorporating Arene Ruthenium Complexes - (:unkn) unknown (My University, 2025)
Introduction of transition metal in the self-assembly of discrete supramolecular structures has recently received a great attention. Both, two- and three-dimensional structures, are found in the literature and the interest in these complex systems lie in the scientific field of chemistry (recognition and selective transformations), biology (translocation of drugs across membranes, biomimetics), and material science (construction of macroscopic architectures and devices at the molecular level). Their synthesis involves a directional-bonding approach in which the metal centres, the multibranched ligands, or a combination of both, control the geometric shapes or polyhedra of the resulting assemblies. When systems containing ruthenium atoms in a two-dimensional fashion are relatively common, three-dimensional structures incorporating ruthenium atoms are scarce. This project originates from the introduction of arene ruthenium building blocks in the self-assembly with 2,4,6-tri(pyridyl)-1,3,5-triazine subunits of hexanuclear metalloprisms. The synthesis of these new metalla-prismatic compounds have opened a wide perspective for bio- and nano-applications and therefore this research project intends to exploit the potential of arene ruthenium moieties in self-assemblies in order to design nano-structured molecules such as supramolecular squares and rectangles, chiral triangular prisms and supramolecular host-guest systems.
Keywords: Supramolecular Assemblies; Arenes; Ruthenium; Bioinorganic; Anticancer Agents; Supramolecular chemistry; Drug delivery